Muslim Intention to Visit Halal Tourism Destination in West Java: Halal Literacy Mediation Effect - Lu'liyatul Mutmainah; Listia Andani; Nuryanti Taufik; Iffah Hafizah (Department of Islamic Economics, IPB University, 2025)
Tourism serves as a gateway to several industrial sectors that are vital to the country's economy. This study aims to investigate the variables influencing the Muslim intention to travel to West Java's halal tourism destination. The Theory of Planned Behaviour (TPB), which is composed of Perceived Behavioural Control (PBC), Attitude towards Behaviour (ATB), and Subjective Norms (SN), is used in this study. In addition, electronic word-of-mouth (e-WOM) and an intervening variable called Halal Literacy (HL) were included in this study. The Partial Least Square Structural Equation Modelling (PLS-SEM) analytical method will be applied in this study with 210 respondents. The study's findings demonstrate that HL and PBC influence the Muslim intention to travel to West Java's halal tourism destinations. In addition, PBC and SN significantly influence HL. However, ATB, e-WOM and SN do not influence to Muslim intention. Additionally, PBC and SN significantly impact to Muslim intention indirectly through halal literacy. Muslim populations should increase halal literacy including halal tourism. Internet media can provide valuable information about reviews of current halal tourist attractions. The synergy between the government, industry players and other stakeholders to support the halal tourism ecosystem in West Java needs to be carried out.